Analisis Peranan Akuntansi Lingkungan Sebagai Pertanggungjawaban Perusahaan Yang Berkelanjutan (Sustainable Company) - Muhammad Al-Ghifari; Ersi sisdianto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The corporate world as a whole sometimes compromises social and environmental issues for the sake of profit. where investors are not the only beneficiaries of the company's operational commitment to social responsibility and environmental protection, that is, investors receive the highest profits. This research uses descriptive methodology and a literature review research design which aims to examine the role of environmental accounting for companies in a sustainable manner. Based on the findings, to emphasize concern and commitment in carrying out mandatory and voluntary social and environmental tasks in a sustainable way, the 3P concept (People, Planet and Profit) is very important to be integrated and managed well within the organization.